A scoping review on the association of early childhood caries and maternal gender inequality - Ivy Guofang Sun; Duangporn Duangthip; Charis Hiu-Kei Kwok; Chun Hung Chu; Yasmi O. Crystal; Robert J. Schroth; Carlos Alberto Feldens; Jorma I. Virtanen; Ola Barakat Al-Batayneh; Balgis Gaffar; Tshepiso Mfolo; Maha El Tantawi; et al. (BMC, 2023)
Abstract Aim The objective of this scoping review is to present current evidence regarding the association between early childhood caries (ECC) and maternal-related gender inequality. Methods Two independent reviewers performed a comprehensive literature search using three databases: EMBASE, PubMed, and Web of Science. Literature published in English from 2012 to 2022 was included in the search and was restricted to only primary research by using the following key terms: "dental caries", "tooth decay", "gender", "sex", "preschool", "toddler," and "infant". The included studies were limited to those reporting an association between ECC and maternal aspects related to gender inequality. Titles and abstracts were screened, and irrelevant publications were excluded. The full text of the remaining papers was retrieved and used to perform the review. The critical appraisal of selected studies was guided by the Joanna Briggs Institute (JBI) Critical Appraisal Tools. Results Among 1,103 studies from the three databases, 425 articles were identified based on publication years between 2012 and 2022. After full-text screening, five articles were included in the qualitative analysis for this review. No published study was found regarding a direct association between ECC and maternal gender inequality at the level of individuals. Five included studies reported on the association between ECC and potential maternal-gender-related inequality factors, including the mother's education level (n = 4), employment status (n = 1), and age (n = 1). Regarding the quality of the included studies, out of five, two studies met all JBI criteria, while three partially met the criteria. Conclusions Based on the findings of this scoping review, evidence demonstrating an association between gender inequality and ECC is currently limited.